2018
DOI: 10.1155/2018/3082507
|View full text |Cite
|
Sign up to set email alerts
|

Tetramethylpyrazine and Paeoniflorin Inhibit Oxidized LDL‐Induced Angiogenesis in Human Umbilical Vein Endothelial Cells via VEGF and Notch Pathways

Abstract: Atherosclerotic plaque angiogenesis is key factor in plaque instability and vulnerability, and low concentrations of oxidized low density lipoprotein (ox-LDL) promote the in vitro angiogenesis of endothelial cells and play an important role in plaque angiogenesis. Ligusticum chuanxiong Hort. and Radix Paeoniae Rubra herb pair in Chinese medicine obtains the optimum therapeutic efficacy in atherosclerosis, and their major active ingredients tetramethylpyrazine (TMP) and paeoniflorin (PF) are reported to allevia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…6 b) could regulate the expression of VEGF. For example, some researchers proved that baicalin [ 33 , 34 ], paeoniflorin [ 35 38 ] and stigmasterol [ 39 ] reduced the expression of VEGF and had a powerful effect on anti-angiogenesis, which were consistent with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…6 b) could regulate the expression of VEGF. For example, some researchers proved that baicalin [ 33 , 34 ], paeoniflorin [ 35 38 ] and stigmasterol [ 39 ] reduced the expression of VEGF and had a powerful effect on anti-angiogenesis, which were consistent with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…Studies have shown that Panax notoginseng saponins reduce advanced glycosylation end product-induced apoptosis of human umbilical vein endothelial cells (HUVECs) by upregulating silent mating type information regulation 2 homolog 1 (SIRT1) [ 18 ]; these saponins also protect the microvessels of the brain by activating the phosphoinositide 3-kinase (PI3K)/Akt/nuclear factor erythroid 2-related factor 2 (Nrf2) antioxidant signaling pathways [ 19 ]. Studies on paeoniflorin have also confirmed its vasoprotective effects [ 20 , 21 ]. Ligustrazine has an inhibitory effect on platelet adhesion, and its mechanism involves the inhibition of p38 mitogen-activated protein kinase (MAPK) and nuclear factor-kappa B (NF- κ B) signaling pathways to downregulate endothelial inflammation [ 22 ].…”
Section: The Mechanisms Underlying the Antiplatelet Effect Of Pbcrbscmmentioning
confidence: 99%
“… Name Active components Biological activity Mechanism of action References Morinda officinalis Iridoids glycoside Antiapoptotic and anticatabolic, anti-inflammatory ↓ Proinflammatory cytokines ↓ MMP-3 and MMP-13 ( Wang et al., 2014 ) Resveratrol Phytoalexin, polyphenolic Regulates apoptosis, degrades extracellular matrix and protects chondrogenesis ↑ Sirt1 ↓ MMP1, MMP3 and MMP13, NF-κB and p38MAPK pathways. ( Liu et al., 2017b ; Jin et al., 2018 ; Wang and Bai, 2019 ) Rhizoma atractylodis macrocephalae Sesquiterpene, atractylenolide Promotes chondrogenic differentiation ↓Osteoclast differentiation ( Li et al., 2012 ) Fructus psoraleae Volatile oil, coumarin, flavones, lipids, resins Promotes viability and cartilaginous formation ↑ Type II collagen ↑ Aggrecan, and Sox-9 ( Pan et al., 2016 ) Semen plantaginis Flavonoids, triterpenoids, iridoid glycosides Antioxidant ↓VEGF, HIF-1α ( Tzeng et al., 2016 ) Hesperetin Flavonoids Antioxidant and antiapoptotic TLR4/NF-κB, Nrf2 pathways ( Chen et al., 2019 ; Muhammad et al., 2019 ) Paeoniflorin Paeoniflorin Angiogenesis ↓VEGF/VEGFR2 ↓Jagged1/Notch1 ( Yuan et al., 2018 ) Daidzein Flavonoids, isoflavones Antioxidant ( Yi et al., 2019 ) Curculigo orchioides Phenols and phenolic glycosides Antioxidant ↑Caspase-3 and caspase-8, ROS-mediated, ↓Bcl-2 ( Hejazi et al., 2018 ) Paeonol Paeonol Antiapoptotic a...…”
Section: Biological Activities For the Selection Of Tcm Treating Tdmentioning
confidence: 99%